Assessment of Nurses Knowledge about Transmission and Prevention for Hepatitis B Virus Infection by instruments in Operating Room at Wasit Teaching Hospital - Ahmed H. Hilal; Juma Redha (Kufa Journal for Nursing Sciences)
Background: The hepatitis B virus causes a potentially fatal liver infection called hepatitis B. (HBV). It is a significant global health problem. It can lead to chronic liver disease and infection, as well as an increased risk of death from cirrhosis and liver cancer. Objectives: To assess Nurses Knowledge about transmission and prevention of hepatitis B virus infection by instruments in operating room. And find out the relationship between demographic characteristics and the variables. Methods: A descriptive study was carried out at Al-Zahraa Teaching Hospital and Al-Karama Teaching Hospital in Wasit City. From the period September 28th 2020until of February 6th, 2021.A non-probability (convenience) sample of (60) nurses working Operating Room in Al-Zahraa Teaching Hospital and Al-Karama Teaching Hospital was used. The tool used in the study was a self-administered structured questionnaire. The data was collected by self-reporting technique. Data was analyzed by using descriptive and inferential statistical data analysis. Results: the study results shows that nurses are with age group of 29-34 year (31±6 years), shows the high percentages were refer to female nurses (83.3%). the majority of the staff are nursing school graduated, shows the year of experience in nursing field is referring to 6-10 year (56.7%). Conclusion: the study concluded that the Knowledge of Nurses' was Poor knowledge; also there is no relationship between Knowledge Regarding prevention of hepatitis B virus in operating room and age and educational level. There was poor knowledge and in total knowledge there is non-significant deferential except in two domain (nurses knowledge about prevention of hepatitis B virus) and (nurses knowledge about Nursing role in operating room to prevent Hepatitis B virus. Recommendations: Training course is necessary to increase nurses’ knowledge toward preventing of HBV in operating room, and regulate continuing education curriculum for all nurses an operating room-specific.